2018
DOI: 10.1111/den.13038
|View full text |Cite
|
Sign up to set email alerts
|

Challenges associated with the pathological diagnosis of colorectal tumors less than 10 mm in size

Abstract: Various techniques including cold snare polypectomy and endoscopic mucosal resection are used for the removal of small colorectal polyps. Specimens of resected polyps are prepared in pathology laboratories and analyzed to make a pathological diagnosis. However, reports on how different resection methods influence the pathological diagnosis are limited. This article discusses the problems associated with the failure of polyp retrieval and fragmentation of small specimens during collection and the effects of cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 21 publications
(32 reference statements)
2
18
0
Order By: Relevance
“…9 Regarding the efficacy of CSP, an analysis based on colonic polyps sized ≤10 mm reported that polyp retrieval failure occurred in 7% of CSP cases. 10 Histologically, unclear margins were observed in 36% of CSP cases for which pathological diagnosis was possible. 10 Another study on colonic polyps reported that only 2% of CSP samples included the submucosa.…”
Section: Cold Snare Polypectomy For Nadetsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Regarding the efficacy of CSP, an analysis based on colonic polyps sized ≤10 mm reported that polyp retrieval failure occurred in 7% of CSP cases. 10 Histologically, unclear margins were observed in 36% of CSP cases for which pathological diagnosis was possible. 10 Another study on colonic polyps reported that only 2% of CSP samples included the submucosa.…”
Section: Cold Snare Polypectomy For Nadetsmentioning
confidence: 99%
“…10 Histologically, unclear margins were observed in 36% of CSP cases for which pathological diagnosis was possible. 10 Another study on colonic polyps reported that only 2% of CSP samples included the submucosa. 11 Therefore, there are still concerns about the application of CSP for high-grade adenomas or carcinomas that need resection including the submucosal tissue.…”
Section: Cold Snare Polypectomy For Nadetsmentioning
confidence: 99%
“…37 In addition, failure of polyp retrieval and fragmentation of small specimens during collection was associated with the effects Cold snare polypectomy 375 of certain parameters on the pathological diagnosis, particularly with regard to surgical margins. 38,39 Therefore, an endoscopy biomarker of effective and safe cold snare polypectomy technique needs to be established in terms of complete removal of non-pedunculated colorectal polyps ≤10 mm.…”
Section: Future Of Cold Snare Polypectomymentioning
confidence: 99%
“…Another cold snare polypectomy study found that 27.8% of excised polyps that were 2–14 mm in diameter did not contain muscularis mucosae, implying incomplete resection for larger polyps in the vertical margins . In addition, failure of polyp retrieval and fragmentation of small specimens during collection was associated with the effects of certain parameters on the pathological diagnosis, particularly with regard to surgical margins . Therefore, an endoscopy biomarker of effective and safe cold snare polypectomy technique needs to be established in terms of complete removal of non‐pedunculated colorectal polyps ≤10 mm.…”
Section: Future Of Cold Snare Polypectomymentioning
confidence: 99%
“…Several possible factors are suspected for the pathological diagnosis of unclear cut‐end or NNP, such as the processes of polyp resection, polyp retrieval, and pathological sample manufacturing 9 . Considering the polyp retrieval factors, specimen retrieved by suctioning through the suction channel is often fragmented even if en bloc resection was achieved, which may affect the pathological evaluation 10,11 . At this point, we focused on the suction valve, which is one of the most intricate parts in the endoscope.…”
Section: Introductionmentioning
confidence: 99%